Evolution of Diplodocid Sauropod dinosaurs with emphasis on specimens from Howe Ranch, Wyoming (USA) - Tschopp, Emanuel (2013)
Diplodocidae are among the best known sauropod dinosaurs. Several species were described in the late 1800s or early 1900s. Since then, numerous additional specimens were recovered in the USA, Tanzania, Portugal, as well as possibly Spain, England, and Asia. To date, the clade includes about 12 to 15 different species, some of them with questionable taxonomic status (e.g. ‘Diplodocus’ hayi or Dyslocosaurus polyonychius). However, intrageneric relationships of the multi-species, iconic genera Apatosaurus and Diplodocus are still poorly known. The way to resolve this issue is a specimen-based phylogenetic analysis, which was done for Apatosaurus, but is here performed for the first time for the entire clade of Diplodocidae. New material from different localities and stratigraphic levels on the Howe Ranch (Shell,Wyoming, USA) sheds additional light on the evolution of Diplodocidae. Three new specimens are described herein, considerably increasing our knowledge of the anatomy of the group. The new specimens (SMA 0004, SMA 0011, and SMA 0087) represent two, to possibly three new diplodocid species. They preserve material from all parts of the skeleton, including two nearly complete skulls, as well as fairly complete manus and pedes, material which is generally rare in diplodocids. Thereby, they considerably increase anatomical overlap between the sometimes fragmentary holotype specimens of the earlier described diplodocid species, allowing for significant results in a specimenbased phylogenetic analysis. Furthermore, clavicles and interclavicles are identified, the latter for the first time in dinosaurs. Their presence seems restricted to early sauropods, flagellicaudatans, and early Macronaria, and might thus be a retained plesiomorphy, with the loss of these bones being synapomorphic for Titanosauriformes and possibly Rebbachisauridae. The new material allows to test previous hypotheses of diplodocid phylogeny. In order to do so, any type specimen previously proposed to belong to Diplodocidae was included in the study, as are relatively complete referred specimens, in order to increase the degree of overlapping material. For specimens subsequently suggested to be non-diplodocid sauropods, their hypothesized sister taxa were included as outgroups. The current phylogenetic analysis thus includes 76 operational taxonomic units, 45 of which belong to Diplodocidae. The specimens were scored for 477 morphological characters, representing one of the most extensive phylogenetic analyses done within sauropod dinosaurs. The resulting cladogram recovers the classical arrangement of diplodocid relationships. Basing on a newly developed numerical approach to reduce subjectivity in the decision of specific or generic separation, species that have historically been included into well-known genera like Apatosaurus or Diplodocus, were detected to be actually generically different. Thereby, the famous genus Brontosaurus is resuscitated, and evidence further suggests that also Elosaurus parvus (previously referred to Apatosaurus) or ‘Diplodocus’ hayi represent unique genera. The study increases our knowledge about individual variation, and helps to decide how to score multi-species genera. Such a specimen-based phylogenetic analysis thus proves a valuable tool to validate historic species in sauropods, and in paleontology as a whole.